Implementasi Nilai Pendidikan Islam dalam Meminimalisir Perilaku Konsumtif pada Remaja - Indri Saputri; Syamsir Syamsir; Hardianto Rahman (Lembaga Penelitian dan Pengabdian Masyarakat IAI Muhammadiyah Sinjai, 2022)
This study aims to describe the consumptive behavior of adolescents in Palattae Village, Kahu District, Bone Regency; and the Implementation of the value of Islamic education on adolescent consumptive behavior in Palattae Village, Kahu District, Bone Regency. This research is included in the type of naturalistic research using a qualitative approach. The subjects in this study were the people of Palattae Village, the northern neighborhood, the middle neighborhood, the eastern neighborhood, and the southern neighborhood who represented the research informants. While the object of research is the consumptive behavior of adolescents in Palattae Village by using a purposive sampling technique. The results showed that of 14 teenagers, there are 11 teenagers have minimized their consumptive behavior because they are able to buy goods based on their needs, buy something in moderation, are more interested in shopping in the market than shopping online because of shipping discounts, not buy goods because the packaging is unique, cute and attractive and does not follow current trends or fashions. Then there are 3 teenagers who do consumptive behavior; it can be concluded that in the indicator of the value of faith there are 14 teenagers who have implemented the value of faith in shopping. In the indicators of the value of worship, there are 11 teenagers who have implemented the value of worship in shopping, then there are 3 teenagers who have not implemented the value of worship. In the indicators of moral values, there are 10 teenagers who have implemented moral values, there are 4 teenagers who have not implemented moral values.